2012
DOI: 10.1080/10473289.2011.636862
|View full text |Cite
|
Sign up to set email alerts
|

Thermal inactivation of Bacillus anthracis surrogate spores in a bench-scale enclosed landfill gas flare

Abstract: A bench-scale landfill flare system was designed and built to test the potential for landfilled biological spores that migrate from the waste into the landfill gas to pass through the flare and exit into the environment as viable. The residence times and temperatures of the flare were characterized and compared to full-scale systems. Geobacillus stearothermophilus and Bacillus atrophaeus, nonpathogenic spores that may serve as surrogates for Bacillus anthracis, the causative agent for anthrax, were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Efficient inactivation of spores is of critical importance for a wide range of applications, including biodefense, food safety, environmental protection, and medical device sterilization (4)(5)(6). Spores are known to be more resistant to inactivation by heating, radiation exposure, and chemical decontamination than their corresponding vegetative cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient inactivation of spores is of critical importance for a wide range of applications, including biodefense, food safety, environmental protection, and medical device sterilization (4)(5)(6). Spores are known to be more resistant to inactivation by heating, radiation exposure, and chemical decontamination than their corresponding vegetative cells.…”
mentioning
confidence: 99%
“…While various methods, including heating, chemical treatment, radiation, and UV treatment, have been used to inactivate spores (4,6,7), thermal inactivation is often the method of choice for many applications (8). Thermal inactivation of Bacillus spores in laboratory studies is most often achieved by wet heat in which spores are fully hydrated during heating (9)(10)(11) or dry heat in which dry spores are heated on a solid substrate, in an ampoule heated by an oil bath, in a hot air plume, or by infrared heating (5,8,(12)(13)(14)(15)(16)(17)(18)(19)(20). It has long been observed that spores are much less resistant to heat in a well-hydrated environment than in a dry state (4).…”
mentioning
confidence: 99%